Anti-wear behaviour of silver nanoparticles on Al-Si alloy. (2nd June 2021) - Akgul, Yasin; Simsir, Hamza
Abstract: In recent years, studies have shown that using nanoparticles (NPs) as lubricant additives lead to the enhancement of the anti-wear behaviour of oils. In this study, the anti-wear behaviour of silver (Ag) NPs which were capped with polyvinyl alcohol and sodium citrate were investigated for three different sliding speeds (2, 3 and 4 mm s −1 ) under two different loads (30 and 50 N). Results show that the AgNPs led to a decrease in friction and wear due to the formation of a tribofilm and a rolling effect. However, influence of the AgNPs declined at higher loads while increasing at higher speed test conditions. Also, both stabilising agents underwent disordering of AgNPs morphology and size successively under the applied loads.